Palbociclib Suppresses the Cancer Stem Cell Properties and Cell Proliferation Through Increased Levels of miR-506 or miR-150 in Panc-1 and MiaPaCa-2 Cells - RENCÜZOĞULLARI, ÖZGE; ARISAN, ELİF DAMLA (TUBITAK Scientific & Technical Research Council Turkey, 2022)
The prognostic characteristics of pancreatic cancer (PC) are determined by the contributing factors from the tumor microenvironment. Leptin is a critical oncogenic factor released by adipocytes as an adipokine into the tumor microenvironment, where it promotes tumor development by activating cancer stem cell (CSC) molecular regulators Notch, Hedgehog, and Wnt/(3-catenin signaling. One of the downstream targets of these pathways is CDK4/6 and cyclin D which is controlled by P16 INK4A that is highly mutated in PC. Therefore, the purpose of this study was to determine the effect of a CDK4/6 inhibitor, palbociclib, on Leptin-induced PC cells and to target the Notch, Hedgehog, and Wnt/(3-catenin signaling pathways via miR-150, miR-506, and miR-208 modulation. Leptin treatment increased the ability of Panc-1, MiaPaCa-2, and Capan-2 cells to proliferate and decreased the effect of palbociclib. Additionally, tumorspheres were generated from Leptin-treated (Leptin+) and Leptin-untreated (Leptin-) Panc-1 and MiaPaCa-2 cells and transfected with miR-506, miR-150 (tumorsuppressor miRNAs), or anti-miR-208 (oncomiR), followed by palbociclib treatment. Forced expression of miR-506 or miR-150 significantly increased the susceptibility of Leptin+ cells to palbociclib treatment by inhibiting colony and tumor spheroid formation, and CD44 expression in Panc-1 and MiaPaCa-2 cells. Additionally, the increased miR-150 expression is more effective at inhibiting N-cadherin, (3-catenin, p-GSK3(3, Notch, and Wnt5a/b expression in Leptin-/+ Panc-1 and MiaPaCa-2 cells. As a result, palbociclib suppressed the CSC profile induced by leptin treatment, inhibiting both tumorsphere forms and leptin-targeted signaling pathways, thereby disabling the Panc-1 and MiaPaCa-2 cells??? resistance mechanism. Increased expression of miR-506 or miR-150 and inhibition of miR-208 enhanced sensitivity of Panc-1 and MiaPaCa-2 Leptin-/+ cells to palbociclib treatment. As a result, this study proved that combining inhibitors of CSC molecular regulators with palbociclib improves the success rate of inhibition of PC cell proliferation.
Keywords: Pancreatic Cancer; CDK4/6 Inhibitor; miR-506; miR-150; miR-208; Wnt/ ß-catenin; Leptin